Strategi Pembelajaran untuk Mengatasi Perbedaan Kebutuhan Belajar dan Keterlambatan Membaca Siswa Kelas IV di SD IT Aziziyyah Pekanbaru (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
Differences in learning needs and delays in reading are common problems that are often encountered among grade IV elementary school students. This situation can have an impact on students' academic achievement if not resolved with effective learning methods. The purpose of this study is to describe the learning methods used by teachers to deal with differences in learning needs and reading delays in grade IV elementary school students. This study uses a qualitative approach by collecting data through observation, interviews, and documentation. The findings of this study show that successful learning methods include different learning, the application of multisensory methods, remedial, individual mentoring, and the use of various learning media that are innovative and interesting for students. This method is able to help students who have difficulty reading without interfering with the learning process of other students. With the sustainable and appropriate application of learning methods, teachers can create an inclusive learning experience, support the development of students' reading skills optimally, increase learning motivation, and build students' confidence and independence in overcoming academic challenges.